EQUIPMENT LEISURE AND SPORT IN SQUARES: SUPPORT TO PUBLIC IN POLITCO ARAXÁ (Fiep Bulletin - online, 2011)
The use of urban space and the construction and animation of leisure facilities are a fundamental part of leisure policy. The objective of this research is to contribute to the formulation of public policy for sport and leisure for the city of Joinville, specifically the axes of space and equipment in parks. The research encompassed the entire universe of products connected to physical recreation and sports, maintained by the municipal government. The squares were divided by sectors (west, east, south, north and center). The research presents a qualitative was performed using a combination of research literature, documentary and field. Field research was conducted through questionnaires to managers of sport and leisure in the last ten years, professionals responsible for activities in the equipment and patrons of the equipment. In addition to the questionnaires were used to observe the equipment during the period of July two thousand and nine, in morning, afternoon and night in order to evaluate which activities are most developed, what age range and gender of the participants. This research provided an opportunity to survey the conditions of the squares, the degree of their use, as well as who and how the activities are developed in places. It is evident that the squares of Araxá not have public policies consistent leisure to meet the local population. We note also that the managers who were responsible for the directory of sport and leisure in the city, showed a total lack of preparation and especially the lack of support for project development and leisure activities. Finally this study and analyzing the problems of equipment squares, allowed to support public policies of recreation for the city, because the results were presented to the municipal government will have the responsibility to manage the city in the next quadrennium.
Keywords: Public Policy; Sports and Leisure